Wykorzystanie leasingu w opinii menedżerów małych i średnich przedsiębiorstw - Łapińska, Anna; Okręglicki, Artur (The Use of Leasing in Opinions of Managers of Small and Medium Enterprises, 2006)
Leasing becomes a very popular source of financing investments in Polish firms. The most interested in this financing form are small and medium enterprises, which because of a not good financial condition and low value of their assets, have a more difficult access to the external financing, especially bank credits. Leasing is also often used because of its numerous advantages.The aim of this paper is to show the results of a questionnaire research concerning the range, importance and ways of leasing using. The survey was carried out among 202 small and medium enterprises at the beginning of 2005. The analysis of lessees opinions about this financing form proves that Polish leasing market has considerable prospects to develop in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 40-46